FUNCTIONAL INTERACTIONS OF THE NERVOUS, IMMUNE, AND ENDOCRINE SYSTEMS IN HUMAN PHYSIOLOGY - Nurimova Diloram Majidovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract From the perspective of modern science, the study of various aspects of the functioning of a single neuroimmunoendocrine system is one of the most pressing problems of experimental medicine and biology. A significant number of facts have been accumulated that consider the immune system together with the nervous and endocrine systems as a multi-component morphofunctional General regulatory system. The interaction of the nervous, immune and endocrine systems ensures the normal functioning of the body, and, undoubtedly, these three systems maintain the constancy of the body’s environment, serving as a "triangle of homeostasis". The study of morphofunctional bases of General regulatory reactions, mechanisms of cell signaling in the formation of connections between various structures of the neuroimmunoendocrine system in order to preserve homeostasis is relevant.